Examination of The Metaphoric Perceptions of Fathers with Child 0-6 Aged Upon the Experience of “Being a Father” - Özlem Haskan Avcı; Tolga Zencir (e-Kafkas Eğitim Araştırmaları Dergisi, 2023)
The current study aims to determine the metaphors expressed by fathers of 0-6 years old children regarding their "becoming a father" experiences and to explore the underlying elements of these metaphors. Thus, the study was carried out with a phenomenological method, one of the qualitative research methods. The study group of the research consists of 90 fathers with children between two months and six years. The data of the research was collected both online and face-to-face. Obtaining data on the experience of "becoming a father" was "becoming a father …. like/similar; Because, …" was obtained by filling in the blanks of the expression. The content analysis method, frequently used in qualitative research methods, was analyzed using the MAXQDA (20.2.2) program. For the reliability of the data, the mean reliability index of the encoders was checked, and the reliability index in this study was obtained as 81%. Fathers stated a total of 96 metaphors, and the metaphors they expressed the most were listed as "being a superhero," "great plane tree," "good news," "school," "rainbow," "being a cloud," "rebirth," "gift." These metaphors are emphasized as positive expressions. According to the analysis of the generated metaphors, a total of 3 themes (Interaction with the Child, Contributing to the Well-Being of the Fathers, and Perceived Fatherhood Duties) were determined. A total of two categories were analyzed in the theme of Interaction with the Child: The learning-teaching process and gamification. There are three categories in the theme of contributing to the father's well-being: Relaxing metaphors and positive life news that are stated as a basic need. Two categories were analyzed in the theme of perceived paternity duties: "Responsibility and Accessibility" and "Being a Role Model."